Implementasi Kebijakan Pengembangan Kawasan Wisata Sejarah Peneleh di Kota di Kota Surabaya - Andrea Rumangkang , Vabianus Hendrix; Sumartono, Sumartono; Hermawan, Romy (Jurnal Ilmiah Administrasi Publik, 2025)
The development of historical tourism areas such as Kampung Peneleh in Surabaya, which includes notable sites like the Peneleh Dutch Cemetery and the Birthplace of Bung Karno, has become a strategic priority to preserve cultural heritage and promote local economic growth. This area has been designated as a cultural heritage site through Surabaya City Regulation No. 1 of 2024. However, the implementation of development policies continues to face challenges, including limited funding, low community participation, and weak coordination among stakeholders. This study aims to analyze policy implementation using a literature review method based on Grindle's theory, with a PRISMA-based approach applied to 40 references. The findings identify four key factors for successful policy implementation: clarity of objectives, availability of resources, community involvement, and effective coordination. Nevertheless, the lack of adaptive local strategies and inadequate monitoring and evaluation mechanisms remain significant challenges. The study recommends formulating clear performance indicators, strengthening public-private partnerships, digitalizing promotional efforts, and enhancing community participation to support cultural preservation, economic growth, and sustainable development.